Mortierella species from declining Araucaria araucana trees in Patagonia, Argentina. Issue 3 (11th April 2020) - Vélez, María L.; Marfetán, Jorge A.; Salgado Salomón, María E.; Taccari, Leonardo E.
Abstract: Since 2015, Araucaria araucana, an ecologically and economically important conifer native to Argentina and Chile, has suffered an unusual partial death of the crown throughout almost all of the distribution range in Argentina. No primary pathogen or pest was evident, associated with the phenomenon. Isolates of Mortierella, a poorly studied fungal genus in Patagonia, were obtained from the margins of necrotic phloem tissue of symptomatic trees. Five species of Mortierella were isolated from affected tissues. In inoculation tests, Mortierella alpina and M. aff . basiparvispora were pathogenic to A. araucana . These species caused necrosis of phloem, leading to chlorosis, foliar desiccation and eventually death, demonstrating that Mortierellales may play a role in the decline of the tree.